Homo historicus as a History-Creator. Paweł Jasienica and His Author’s Vision of Polish History - Pomorski, Jan (Sensus Historiae, 2019)
Paweł Jasienica’s reflection on the history of Poland has been considered in this study. Jasienica, a well-known Polish historical essayist and historiosopher, is the author of such bestsellers as The Piasts’s Poland, The Jagiellons’ Poland, and Polish-Lithuanian Commonwealth. His original method of storytelling has allowed him to be recognized also as one of the best Polish historical novelists. Jasienica teaches us, first and foremost, that historians are not only storytellers but also public persons/figures who must be aware of social and human responsibility of their own meta-narrations.